Characterization of the quality criteria of medicine courses in the regional accreditation system of university courses (ARCUSUR) (Journal on studies and research of academic knowledge, 2022)
This article presents the characterization of the quality criteria of medicine courses according to the ARCU-SUR model. A bibliographic review is carried out on the dimensions, criteria and indicators. The type of research is descriptive, with the documentary method, qualitative approach and non-experimental design. The population is the peer reviewers of ARCU-SUR and references in the area of accreditations in the area of medicine. It is concluded that regional quality criteria lead to a convergence of national higher education evaluation systems between countries, despite the diversity of national systems and their evaluation systems, with the main objective of evaluating the quality of the career. and thus, guarantee the integral formation of the medical student.
Keywords: Criteria; Quality; Accreditation; ARCU-SUR; Medicina